Pengaruh karakter guru pendidikan agama Islam terhadap semangat belajar siswa - Diazhady, Diego Irfana; Alwahid, Muhamad Azhar; Andestend (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2026)
This study aims to examine the influence of Islamic Education (PAI) teachers' character on students' learning enthusiasm at SMK Budiniah. Islamic Education plays a strategic role in shaping students' character and morals. However, low student motivation towards PAI subjects remains a common issue. One suspected contributing factor is the character of the teachers, who serve as direct role models during the learning process. This research employs a quantitative approach with an associative survey method. Data were collected through questionnaires and documentation, involving a population of 206 students and a sample of 104 students selected using purposive sampling techniques. The research instrument's validity and reliability were tested using SPSS. The results indicate a significant influence of PAI teachers' character on students' learning enthusiasm at SMK Budiniah. Teachers with good character traits such as honesty, trustworthiness, fairness, and the ability to build effective communication and exemplary behavior can positively enhance students’ motivation and learning enthusiasm. These findings underscore the importance of teachers' character in supporting an effective learning process, particularly in religious education. Therefore, strengthening teachers' character is a crucial aspect in efforts to improve the quality of PAI education in vocational high schools. Abstrak Penelitian ini bertujuan untuk mengetahui pengaruh karakter guru Pendidikan Agama Islam (PAI) terhadap semangat belajar siswa di SMK Budiniah. Pendidikan Agama Islam memiliki peran strategis dalam membentuk karakter dan moral peserta didik. Namun, rendahnya semangat belajar siswa terhadap mata pelajaran PAI masih menjadi permasalahan yang sering ditemui. Salah satu faktor yang diduga berpengaruh adalah karakter guru yang menjadi teladan langsung bagi siswa dalam proses pembelajaran. Penelitian ini menggunakan pendekatan kuantitatif dengan metode survei asosiatif. Data dikumpulkan melalui kuesioner dan dokumentasi, dengan populasi sebanyak 206 siswa dan sampel sebanyak 104 siswa yang ditentukan melalui teknik purposive sampling. Instrumen penelitian diuji validitas dan reliabilitasnya menggunakan SPSS. Hasil penelitian menunjukkan bahwa terdapat pengaruh yang signifikan antara karakter guru PAI terhadap semangat belajar siswa di SMK Budiniah. Karakter guru yang baik seperti jujur, amanah, adil, serta mampu membangun komunikasi dan keteladanan yang baik mampu meningkatkan motivasi dan semangat belajar siswa secara positif. Temuan ini menegaskan pentingnya peran karakter guru dalam menunjang proses pembelajaran yang efektif, khususnya dalam pendidikan agama. Oleh karena itu, penguatan karakter guru menjadi aspek krusial dalam upaya meningkatkan kualitas pembelajaran PAI di sekolah menengah kejuruan.